Flexible Electronics: Transparent, Flexible, and Passive Thermal Touch Panel (Adv. Mater. Technol. 9/2016). Issue 9 (December 2016) - Ruoho, Mikko; Juntunen, Taneli; Alasaarela, Tapani; Pudas, Marko; Tittonen, Ilkka
Abstract : In article number 1600204, Ilkka Tittonen and co‐workers present a flexible, scalable and highly transparent touch panel design which is based on the Seebeck effect. The image conceptualizes the novel transparent and flexible touch panel. A temperature gradient across the image transports charge carriers within the solid state structure. Through this thermoelectric effect, the heat distribution across the device can be mapped.